INTEGRATION OF PEOPLE'S ECONOMY AND ENTREPRENEURSHIP EDUCATION: MARHAENISM IDEOLOGY AND INDEPENDENT DIMENSION IN P5 PROJECT - Yaqin, Mohammad Nurul; Yasin, Nur Ali (jfpublisher, 2024)
This article discusses the integration of people's economic values derived from the Marhaenism ideology into education through the Pancasila Student Profile Strengthening Project (P5), with a focus on strengthening the Independent dimension and developing entrepreneurship education. Marhaenism as an ideology that sides with the poor emphasizes the importance of economic independence, productive work, and rejection of exploitation. These values are very relevant to the spirit of education that wants to form students who are not only academically capable, but also resilient and empowered socio-economically. Through the literature review method, this article examines the concept of Marhaenism, the principles of people's economy, and their relationship to the Independent dimension in P5. In addition, opportunities and strategies for implementing entrepreneurship education based on local and social values are also discussed. The results of the study show that this integration has the potential to form students who have ideological awareness, are independent in thinking and acting, and are able to become agents of economic change based on social justice. This article recommends the need for policy support, teacher training, and cross-party collaboration to encourage the successful implementation of this integration in educational units.